2016
DOI: 10.1007/s12079-016-0351-9
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-1275 suppresses cell growth, and retards G1/S transition in human nasopharyngeal carcinoma by down-regulation of HOXB5

Abstract: Through analysis of a reported microarray-based high-throughput examination, we found that miR-1275 was significantly down-regulated in nasopharyngeal carcinoma (NPC). While its role and mechanism participated in NPC progression are still little known. Here, we explored the effect of miR-1275 on the progression of NPC. Results demonstrated that miR-1275 was markedly down-regulated in NPC tissues and cell lines. MiR-1275 markedly repressed cell growth as confirmed by CCK8 and colony formation assay, via inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
0
20
0
1
Order By: Relevance
“…24 It was reported that miR-1275 exhibited its tumour suppressive role on nasopharyngeal carcinoma cells by down-regulating oncogenic HOXB5, whose expression was negatively related to miR-1275. 25 In our study, we found that miR-1275 was lowly expressed in glioma and its up-regulation could suppress glioma cell function including proliferation, migration and invasion, as well as induce apoptosis. Our discovery was consistent with the generally reported conclusion that miR-1275 works as a tumour suppressor.…”
Section: Discussionmentioning
confidence: 62%
“…24 It was reported that miR-1275 exhibited its tumour suppressive role on nasopharyngeal carcinoma cells by down-regulating oncogenic HOXB5, whose expression was negatively related to miR-1275. 25 In our study, we found that miR-1275 was lowly expressed in glioma and its up-regulation could suppress glioma cell function including proliferation, migration and invasion, as well as induce apoptosis. Our discovery was consistent with the generally reported conclusion that miR-1275 works as a tumour suppressor.…”
Section: Discussionmentioning
confidence: 62%
“…Over the past decades, the emerging role of ncRNAs, including miRNAs, have been reported in the development of EC radioresistance. [28][29][30][31] In this study, we proved that miR-1275, which has been revealed to exert paradoxical functions in different cancer types, 12,[32][33][34] was down-regulated in radioresistant EC cells. Meanwhile, we illustrated that miR-1275 could increase the sensitivity of EC cells to radiotherapy both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 65%
“…Liu et al have shown that miR-1275 accelerates the proliferation and migration of head and neck squamous cell carcinoma cells [11]. miR-1275 modulates the proliferation of nasopharyngeal cancer cells by targeting HOXB5 [12]. However, the function of miR-1275 in prostate cancer remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The intercommunication between different cells via exosomal miRNAs is suggested to be an important way of interaction between tumor cells and the tumor microenvironment [9]. Multiple studies have been demonstrated that miR-1275 plays an important role in cancer progression [10][11][12]. Using the whole miRNome analysis, Nam et al have shown that miR-1275 is a potential candidate associated with PCa metastasis [13].…”
Section: Introductionmentioning
confidence: 99%